The influencing factors of university-enterprise collaboration - A case study of Tsinghua Unigroup, a spin-off enterprise of a well-known Chinese university - Song, Wanqiu; Mat, Norazila Binti (Edelweiss Applied Science and Technology, 2025)
This paper examines the development of Tsinghua Unigroup Group, a prominent example of a Chinese university spin-off enterprise. It explores the factors influencing the future sustainable growth of university-derived companies through a detailed case study. By analyzing work reports published by Tsinghua Unigroup over recent years and reviewing public interview records of the enterprise’s senior executives, this study summarizes valuable experiences and lessons learned in achieving sustainable development. Throughout its development, Tsinghua Unigroup has accumulated significant expertise and identified critical lessons, which provide new insights, innovative approaches, and effective methods for the sustainable growth of university spin-offs. The research emphasizes that the development of university-derived enterprises relies heavily on support from universities and government agencies, as well as industry-university-research collaborations and human resource management. The findings suggest that these elements are essential for fostering innovation and ensuring long-term sustainability. This study offers new perspectives and strategies that can help university spin-off enterprises avoid common pitfalls and accelerate their progress in scientific and technological innovation and sustainable development, ultimately contributing to the broader economic and technological advancement of the region and country.